INSERTION OF TRAINING AND DEVELOPMENT IN ORGANIZATIONS - Barbosa, Bárbara Santana; Camilo, Karen Fernanda da Silva; de Oliveira, Mara Janaina Gomes (Revista Interface Tecnológica, 2023)
This paper deals with training and development, presenting theoretical knowledge about the relevance of inserting T&D within corporations. Thus, the article has the general objective of validating the importance that the process of training and development of employees add to companies, with the specific objective: addressing the importance of training and development in organizations, Analyzing the responses of participants in the light of the theoretical discussion presented in this work, demonstrating the importance of training for individual and organizational development. From this, a questionnaire containing thirteen questions was applied, two of which were open and eleven were closed.
Keywords: Qualification; Training; Development; Human Resources